First Record of Flavocillium subprimulinum (Cordycipitaceae, Hypocreales) in Mexico: Morphological and Molecular Characterisation, Nematocidal Activity of Its Liquid Culture Filtrates against Haemonchus contortus and Protease Activity - Gustavo Pérez-Anzúrez; Pedro Mendoza-de Gives; Agustín Olmedo-Juárez; María Eugenia López-Arellano; Génesis Andrea Bautista-García; Ana Yuridia Ocampo-Gutiérrez; Elke von Son-de Fernex; Miguel Ángel Alonso-Díaz; Edgar Jesús Delgado-Núñez; Adolfo Paz-Silva (Journal of Fungi, 2024)
This is the first record of the fungus Flavocillium subprimulinum in Mexico. The isolate was taxonomically characterised and cultured in potato dextrose broth (PDB), Czapek–Dox broth (CzDoxB), and sweet potato dextrose broth (SPDB) to obtain its filtrates (FLCF). The nematocidal activity (NA) of three FLCF concentrations was assessed against Haemonchus contortus L3. Protease activity (PA) was assessed with SDS-PAGE, followed by a zymogram. The NA of the FLCF reached 94.43% in PDB and 95.82% in CzDoxB, respectively, at 100 mg/mL. Lower mortality (64%) was found in SPDB at 100 mg/mL. SDS-PAGE showed bands (in PBS) of ~25, ~40, and ~55 kDa. The zymogram showed protein bands (PBs) with PA in the media, including PBs of ~14, ~40, and ~55 kDa. This study establishes the basis for exploring the potential use of this fungus against H. contortus, which is considered the most pathogenic parasite affecting lambs.